THE CIVILIZATIONAL ASPECT OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT IN A GLOBALIZED WORLD - Kleshnia, Hanna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The world we live in is changing so rapidly that even scientists do not have time to comprehend the changes and determine the possibilities for further development. Trying to overcome the contradictions of the socio-cultural heritage of the modern era, humanity seeks to move forward through controlled sustainable development. The trends that began in the 20th century are maturing and operating in new conditions, against the backdrop of new global challenges, which largely determine the nature and result of the implementation of the concept of sustainable development. The aim and tasks are the philosophical analysis of the civilizational dimension of the implementation of the concept of sustainable development as a tool for artificial management of the globalized world. Research methodology is dialectical, sociocultural, systemic, and interdisciplinary methodological approaches, principles of hermeneutics, and historicism. Research results. There are different civilizational theories that substantiate the vector of interaction between different countries and the world community as a whole in order to overcome the global problems of mankind in different ways. From the standpoint of the dialectical law of the mutual transition of quantitative and qualitative changes, the chosen strategy for overcoming global threats does not work. A qualitative leap that characterizes development has not taken place and, based on existing trends, it will not happen in the future. Internal contradictions are in artificial stasis. The dogmatization of goals in the adopted Concept makes it impossible to correct them in accordance with the challenges of the present. In turn, this state contradicts the evolutionary path of development. Discussion. The most appropriate structure of civilizational development in a globalized world is the concept of "worldsystem analysis" proposed by I. Wallerstein. Global patterns and trends are increasingly active on the planet, the nature of which is determined primarily by the interests and capabilities of a small group of the most powerful states, international financial institutions, and transnational corporations (Pavlenko). Conclusions. The concept of sustainable development requires detailed development and philosophical reflection of new development strategies based on objective principles and laws of dialectics.